2013
DOI: 10.1155/2013/461487
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Compound Norcantharidin Induced Apoptosis in Mantle Cell Lymphoma In Vivo and In Vitro through the PI3K-Akt-NF-κB Signaling Pathway

Abstract: This study aimed to elucidate the antitumor activity of norcantharidin (NCTD) against human mantle cell lymphoma (MCL). Cell proliferation and apoptosis were examined by MTS and flow cytometry. Caspase-3, -8, and -9 activities were detected with a colorimetric caspase protease assay. Apoptotic proteins—including PARP, cyclin D1, Bcl-2 family proteins, XIAP, and cIAP I—were studied by western blot. The phosphoinositide 3 kinase (PI3K) inhibitor LY294002 was used to investigate the involvement of the PI3K/Akt si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Interestingly, blocking PI3K-AKT pathway by LY294002 largely abolished the activation of NF-κB induced by TIPE3 overexpression, suggesting that TIPE3 might activate NF-κB through AKT pathway during breast cancer development. This finding was consistent with studies that NF-κB cross-talks with AKT signaling [ 32 , 33 ]. These results indicate that TIPE3 regulates proliferation, migration and invasion by activating AKT and NF-κB pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, blocking PI3K-AKT pathway by LY294002 largely abolished the activation of NF-κB induced by TIPE3 overexpression, suggesting that TIPE3 might activate NF-κB through AKT pathway during breast cancer development. This finding was consistent with studies that NF-κB cross-talks with AKT signaling [ 32 , 33 ]. These results indicate that TIPE3 regulates proliferation, migration and invasion by activating AKT and NF-κB pathways.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, the enhanced proliferation (Figure 8A and 8B ), colony formation (Figure 8C and 8D , Supplementary Figure 5A and 5B ) and migration (Figure 8E and 8F , Supplementary Figure 5C and 5D ) in MCF-7 and MDA-MB-231 cells induced by overexpressed TIPE3 were largely blocked by CAPE or LY294002. Interestingly, the elevation of p-IkBα and p-P65 induced by overexpressed TIPE3 was also largely blocked by LY294002 (Figure 7C and 7D ), suggesting that TIPE3 might activate NF-κB pathway through AKT pathway in breast cancer cells [ 32 , 33 ]. Taken together, these data demonstrate that TIPE3 promotes proliferation, migration and invasion of breast cancer cells by activating AKT and NF-κB pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Till now, no evidence revealed that CagA could act as a transcription factor to regulate gene expression directly, so we presumed that CagA increased DNMT1 expression by disdurbing some key signal pathway in GC. Since AKT has been well known to play a significant role in regulating genes expression and the aforementioned data revealed that P-PDK1 is a known activator and binding partner of AKT [ 19 ], also, it's well established that NFκB is a downstream element of the AKT pathway [ 20 ], so we investigated whether PDK1/AKT-NFKB pathway is involved in DNMT1 upregulation and subsequent MGMT hypermethylation. To this end, the total and phosphorylation protein of PDK1/AKT-NFκB pathway in the nucleus and cytoplasm of cells differently treated were detected.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that NCTD could inhibit the proliferation and induce apoptosis in several cancer cell lines, such as leukemic cells, gallbladder carcinoma cells, colorectal cancer cells [11][12][13], prostate cancer cells [14], mantle cell lymphoma (MCL) [15], and hepatocellular carcinoma cells [16]. In addition, due to stimulating bone marrow and increasing the peripheral leukocytes, NCTD may be a potential chemotherapeutic agent in cancer treatment, and it has attracted considerable attention in recent years [17].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent studies have shown that NCTD inhibited proliferation and migration with enhanced anticancer activity of gefitinib and cisplatin in NSCLC without affecting EGFR signaling [18]. Nevertheless, NCTD can induce growth arrest and apoptosis in MCL cells through the PI3K/Akt signaling pathway [15]. Based on the study that inhibition of PI3K/AKT pathway may effectively overcome HGF-induced resistance to EGFR-TKI [19], we hypothesized that NCTD enhanced anticancer activity of gefitinib due to reversing EGFR-TKIs resistance induced by HGF in EGFR mutant NSCLC.…”
Section: Introductionmentioning
confidence: 99%